Increased Nuclear Transporter Importin 7 Contributes to the Tumor Growth and Correlates With CD8 T Cell Infiltration in Cervical Cancer - Chen, Jing; Hu, Yan; Teng, Yincheng; Yang, BiKang (Frontiers in Cell and Developmental Biology, 2021)
Background: Importin 7 (IPO7), a karyopherin-β protein, is involved in various tumorigenesis and progression abilities by mediating the nuclear import of oncoproteins. However, the exact biological functions of IPO7 remain to be further elucidated. Materials and Methods: TCGA and GEO datasets were used to identify dysregulated expression of IPO7 in various cancers. Gain-of-function and loss-of-function analyses were used to identify the oncogenic functions of IPO7 in vitro and in vivo. Moreover, LC-MS/MS and parallel reaction monitoring analysis were used to comparatively profiled IPO7-related proteomics and potential molecular machinery. Results: Our works demonstrated that the expression of IPO7 was upregulated and was correlated with a poor prognosis in cervical cancer. In vitro and in vivo experiments demonstrated that knockdown of IPO7 inhibited the proliferation of HeLa and C-4 I cells. LC-MS/MS analysis showed that IPO7-related cargo proteins mainly were enriched in gene transcription regulation. Then independent PRM analysis for the first time demonstrated that 32 novel IPO7 cargo proteins, such as GTF2I, RORC1, PSPC1, and RBM25. Moreover, IPO7 contributed to activating the PI3K/AKT-mTOR pathway by mediating the nuclear import of GTF2I in cervical cancer cells. Intriguingly, we found that the IPO7 expression was negatively correlated with CD8 T cell infiltration via regulating the expression of CD276 in cervical cancer. Conclusion: This study enhances our understanding of IPO7 nuclear-cytoplasmic translocation and might reveal novel potential therapeutic targets. The results of a negative correlation between the IPO7 and CD8 T cell infiltration indicate that the IPO7 might play an important impact on the immune microenvironment of cervical cancer.